Schistosoma haematobium treatment in 1-5 year old children: safety and efficacy of the antihelminthic drug praziquantel. - Francisca Mutapi; Nadine Rujeni; Claire Bourke; Kate Mitchell; Laura Appleby; Norman Nausch; Nicholas Midzi; Takafira Mduluza (Public Library of Science (PLoS), 2011)
Morbidity due to schistosomiasis is currently controlled by treatment of schistosome infected people with the antihelminthic drug praziquantel (PZQ). Children aged up to 5 years are currently excluded from schistosome control programmes largely due to the lack of PZQ safety data in this age group. This study investigated the safety and efficacy of PZQ treatment in such children.Zimbabwean children aged 1-5 years (n = 104) were treated with PZQ tablets and side effects were assessed by questionnaire administered to their caregivers within 24 hours of taking PZQ. Treatment efficacy was determined 6 weeks after PZQ administration through schistosome egg counts in urine. The change in infection levels in the children 1-5 years old (n = 100) was compared to that in 6-10 year old children (n = 435).Pre-treatment S. haematobium infection intensity in 1-5 year olds was 14.6 eggs/10 ml urine and prevalence was 21%. Of the 104 children, 3.8% reported side effects within 24 hours of taking PZQ treatment. These were stomach ache, loss of appetite, lethargy and inflammation of the face and body. PZQ treatment significantly reduced schistosome infection levels in 1-5 year olds with an egg reduction rate (ERR) of 99% and cure rate (CR) of 92%. This was comparable to the efficacy of praziquantel in 6-10 year olds where ERR was 96% and CR was 67%. INTERPRETATION/SIGNIFICANCE: PZQ treatment is as safe and efficacious in children aged 1-5 years as it is in older children aged 6-10 years in whom PZQ is the drug of choice for control of schistosome infections.